The Fun Way to Face Students Difficulties While Learning English - Serina Serina; Rustan Effendi; Hasmiah Herawaty (English Education : English Journal for Teaching and Learning, 2022)
Learning fun English so far can be done in various ways, and each way creates its own diversity of results. Of course, this can be happened after the teacher knows the situation of the class and students, before preparing teaching plan. The strategy of involving students in learning is a powerful way to support their better understanding, because directly practice what they have learned can support their memory to imprint deeper, especially in auditory, visual, or even kinesthetic learners. The main point is that students are directly involved when learning, not just seeing or hearing but in thinking, speaking, and analyzing learning activities. Considering how difficult it is to keep students interested when learning English, involving them from the start to keep them active, focused, and motivated is a step that can be taken.